LIFE STRUGGLE IN THE FAULT IN OUR STAR BY JOHN GREEN - syaharani, dinar; Englishtina, Inti (LINGUAMEDIA Journal, 2024)
The purpose of this analysis is to describe the main characters and characterizations and find out the theme in The Fault in Our Star. The writer uses qualitative methods to conduct this research. For analysis, the writer uses a qualitative approach. This research is entitled "Life Struggle in The Fault in Our Stars by John Green". The main reason the writer chose this topic is because the novel tells about the life struggle against the characters' illnesses. The second element analyzed in this case is the theme, how does he survive in a sad situation. The third element in the novel that will be discussed is that the writer will discuss in more detail the life struggles faced by the characters in the novel. Finally, the writer hopes that this paper will be useful for the readers, especially to better understand the intrinsic elements of the novel.